Antidiarrhoeal Potential of Secondary Metabolites in Betel Leaf (Piper betle): A Systematic Review with Radar Chart Analysis and AUC Evaluation. - Khrisna Agung Cendekiawan; Kintoko Kintoko; Sapto Yuliani; Linda Suci Anggraeni; Firdha Aprillia Wardhani; Neny Poerwahyuningrum (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Diarrhoea is a widespread gastrointestinal disorder commonly caused by microbial infection, inflammation, or impaired intestinal function. While synthetic antidiarrhoeal drugs are available, their use is often limited by adverse effects and antimicrobial resistance, prompting increasing interest in medicinal plants such as Piper betle (betel leaf). This study systematically reviewed the literature to identify secondary metabolite compounds in Piper betle with antidiarrhoeal potential and to evaluate their biological activities using Radar Chart Analysis (RCA) and Area Under Curve (AUC) methods. A systematic search was performed across PubMed, Scopus, Web of Science, and Google Scholar using predefined keywords. Inclusion criteria comprised studies that investigated Piper betle or its secondary metabolites, reported antidiarrhoeal or related bioactivity, and provided quantitative data suitable for comparison. Studies were excluded if they focused solely on synthetic drugs, were not available in full text, or did not report measurable metabolite data. A total of 35 eligible studies were included after screening 176 records. The findings indicate that flavonoids, polyphenols, tannins, saponins, and catechins in Piper betle contribute to antidiarrhoeal effects through mechanisms that modulate intestinal motility, reduce fluid secretion, activate anti-inflammatory pathways, and exhibit antimicrobial activity. RCA and AUC analyses further demonstrated substantial variability in metabolite composition and antioxidant capacity across studies. Overall, Piper betle exhibits promising therapeutic potential as a natural antidiarrhoeal agent, although further mechanistic and clinical research is warranted.